INFLUENCE OF DIGITAL TECHNOLOGIES ON HUMAN RIGHTS: POSITIVE INFLUENCE, RISKS, TRENDS AND DEVELOPMENT PROSPECTS: (Global and National Experience) - Firuza Khamdamova (International Journal of Innovative Technologies in Social Science, 2020)
The article is devoted to the impact of digital technologies on human rights. The author examines the positive impact of digital technologies on human rights, as well as the negative consequences of digitalization on human rights. The article provides an overview of international standards in this area, examines foreign countries for the protection of human rights in the context of digital transformation. Particular attention is paid to the consideration of measures taken in Uzbekistan in this direction. In conclusion, the author puts forward a number of recommendations for improving international and national mechanisms for ensuring and protecting human rights in the context of digital transformation.